Igniting a revolution at point zero? Exploring the barriers to early learning access in South Africa and the possibility of the social economy : a comparative analysis and study of Smartstart - McCann, Claire Mary (Rhodes University, Faculty of Commerce, Department of Economics and Economic History)
Economic theory suggests that the greatest return to education investment is in the earliest years; early learning and childcare may enhance skill accumulation and mothers' labour market choices. These services may be catalytic, igniting a revolution at point zero that transforms family outcomes and aids development. In South Africa, however, early learning deficits persist. This thesis explores barriers to quality early learning access and the possibility social economy initiatives offer, focusing on social franchises like SmartStart. Document analysis, comparative analysis, and interviews with SmartStart leaders suggest two key barriers. Firstly, where private firms are dominant and ability to pay for services is limited, low-income areas are under-served. For this reason, Polanyi claims that markets should be embedded in institutions. A post-Polanyian approach emphasises the role of social investment states, which focus spending on education and where social protection scaffolds markets, in this regard. The South African state seems to embrace this approach as ECD policy frames early learning as a public good and social investment. However, a second barrier is that an insulated state enables technocratic over democratic embeddedness, with powerful rights-based discourse but poor implementation. In particular, it seems that the state lacks a framework to progressively realise the right to quality early learning. Attempts to enforce high standards are not accompanied by sufficient resources, capacity or collaboration, resulting in sub-standard services and barriers to entry. Even in better resourced contexts (e.g., Basic Education), top-down, technocratic models (re)produce failing systems, where those with means exit in favour of market alternatives. An exploration of other developing countries suggests that this failure, with variations, prevails, but also that possibility exists. In these contexts, states seem more coordinated and responsive when partnering with civil society. In South Africa, the SmartStart model is based on partnership. SmartStart frames itself as a delivery platform, building relationships with local NGOs to simultaneously scale and deepen early learning. Partnerships with communities are crucial, to build demand in a sector whose association with social reproduction means that its economic significance may be overlooked. In addition, SmartStart puts forward a child-centred approach based on a prefigurative vision but also responsive to the realities of under-resourced contexts, aiming to progressively realise rights. Though with some limitations, SmartStart's least-cost innovation for scale provides lessons for the state. As the state's ECD mandate shifts to Basic Education, these findings serve to inform a more effective implementation model, leveraging resources that already exist.
Keywords: Early childhood education -- South Africa; Social economy -- South Africa; Smart Start; Education and state -- South Africa; Social democracy; Dual economy -- South Africa; South Africa Economic conditions 1991-